Why Resilient Leadership Fails to Enhance Employee Performance - Arief Mujiono; Kusuma Chandra Kirana; Syamsul Hadi (SMARTINDO, 2025)
Purpose - This study aims to examine the direct influence of Resilient Leadership on Employee Performance in the local public sector. Design/methodology/approach - A quantitative approach was applied, using data from 100 employees in one of the government offices in Indonesia. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS), which included instrument testing, model fit evaluation, hypothesis testing, and mediation. Originality - This study contributes to the field of leadership and human resource management by emphasizing the limitations of relying solely on Resilient Leadership to improve employee outcomes. Findings and Discussion - Resilient Leadership does not have a significant direct effect on Employee Performance. This indicates that the role of resilient leadership requires the support of other factors to enhance employee performance effectively. Conclusion - The study provides insights that relying solely on resilient leadership is insufficient to drive employee performance, particularly in government institutions that face structural limitations and strict regulations.